Análisis de la aplicación del sistema único de compensación regional sucre y su incidencia en la balanza comercial entre Ecuador y Venezuela - Calderón Borja, Joselin Anabelle (2018)
Within this study called "Analysis of the application of the Regional System of Regional Compensation (SUCRE) and its impact on the trade balance between Ecuador and Venezuela", determining as its main objective to determine the way in which the relationship has been carried out between these nations before and during the use of this system, in order to achieve this, it will be evident if Ecuador has perceived mostly harmful benefits or situations. A bibliographic research was developed in which all the data related to the creation of SUCRE was collected, as well as theories related to international trade such as the balance of payments, the competitive advantage of nations, economic integration and the characteristics of the most important economic integration blocks worldwide……